DYNAMICS OF SERUM BIOCHEMICAL ATTRIBUTES IN INDIGENOUS SIPLI SHEEP BREED KEPT UNDER INTENSIVE FARMING SYSTEM - Musadiq Idris; Umer Farooq; Mushtaq Hussain Lashari; Sumama Qayyum; Ammara Arshad; Umair Riaz; Musarrat Abbas Khan; Iram Fatima; Hafsa Sajjad (Journal of Animal and Plant Sciences, 2024)
The present study is the first record of deducing age-wise and sex-wise normal reference intervals (RIs) for various serum biochemical attributes in apparently healthy Sipli sheep being reared under intensive farming system at Livestock Farm of the Faculty of Veterinary and Animal Sciences (FV&AS), The Islamia University of Bahawalpur (IUB). Blood samples were aseptically collected, serum was harvested and analyzed for serum chemistry analytes through semi-automatic chemistry analyzer using commercial kits. For the sake of analysis, groups were assigned as per age i.e. G1= up till 1year (n= 41), G2= from 1 to 2 years (n= 46), G3= from 2 to 3 years (n= 43) and as per sex i.e. females (n= 79) and males (n= 51). All the overall mean values and RIs for all the studied attributes were within the reference ranges provided in earlier studies for sheep. Bilirubin, Alkaline Phosphatase (ALP) and creatinine were significantly (P≤0.05) lower in females as compared to those in males. However, uric acid was significantly (P≤0.05) higher for females 52.8±2.6mmols/L as compared to 44.5±2.9mmols/L for males. The remaining attributes (Alanine Transaminase, Aspartate Aminotransferase, Total Proteins, Albumin, Glucose, Low Density Lipoproteins, High Density Lipoproteins and Urea) did not differ -significantly (P≥0.05) between male and female sheep under study. For age-related results, only ALP, glucose and HDL were significantly (P≤0.05) different between the three studied age groups of Sipli sheep. The ALP and glucose were higher in G1 animals (up till 1 year) whereas HDL was lower in G2 animals (from 1 to 2 years) as compared to their counter-part groups 1 and 3. The data can be beneficial in diagnostic/prognostic purpose for veterinarians, academicians, researchers and all other stakeholders of sheep-rearing sector in Pakistan as well as for other indigenous sheep breeds being reared under similar climatic conditions throughout the world.
Keywords: Sipli sheep; Serum chemistry; Chemistry analyzers